The Spanish creator Max Aub, witness of his epoch - Echoayeby, Idriss (Journal of Human Sciences, 2021)
This article aims to highlight the value and prestige of one of the most famous, and most important, creators of the twentieth century. It is the illustrious and prolific creator Max Aub, who cultivated almost all literary genres with a huge mastery. It is also regarded as the paradigm of the true intellectual whose greatest interest lies in ethical commitment and, above all, the defence of noble humanitarian causes.This research is centered on demonstrating some important aspects of his creations that combine great artistic ability, moral and political commitment to just causes of the oppressed human, regardless of nationality, race and creed. In this context, we will try to address all these aspects from some of his novels, such as " Valverde Street" (1961) and "Good Intentions" (1954), as well as " Luis Álvarez Petreña " (1934).The principal purpose of this essay is to present to the Arab reader an important intellectual with a specific style, who we need in this difficult situation in which lives the Arab world.